Nanotechnology in biology and medicine : (Taylor & Francis, 2017)
This text is a substantial revision of a major reference work in nanotechnology that details many of the latest developments relating to nanotechnology in biology and medicine. Every chapter has been updated with new material that is being added in the field of molecular medicine. There are revisions within each chapter. The same world-class contributors are involved in the new edition, as well as a number of many new contributors.